International Legal Cooperation of States in the Fight against International Terrorism - S. I. Mukashev (Московский журнал международного права, 2008)
In the doctrine of international criminal law there are two categories of international crime: international crimes and crimes of international character Both of them cause a considerable damage to the international order, peace and security and eventually the interests of each and every county.Terrorism is usually referred to as a crime of international character. Nowadays it can be defined as illegal acts which pose a threat to the international peace and the security of humankind But still there is no unified definition of terrorism while attempts had already been made in the framework of the League of Nations in 1937.The leading role in fight against terrorism belongs to the United Nations 13 Conventions on the issues of terrorism had been adopted in its framework These conventions are of great importance though some things need to be revised and corrected Apart from this UN Secretary General initiated in 2003 an establishment of a special group to monitor the threats to the international peace and security.It is necessary to elaborate on international level a single antiterrorism convention, which could cover all the relevant issues and include the definition of terrorism approve by the majority of states. This fact would enhance the fight of international community against terrorism. Also terrorism can be included in the list of international crimes to be prosecuted for in the framework of the International Criminal Court.